Psychological Distress and Quality of Life Among Infertility Couples Undergoing Infertility Treatment in Malaysia - Farrahdilla Hamzah; Zamzaliza Abdul Mulud; Malini Mat Napes; Sarah Abdul Mubarak; Rosliza Shafie (Fakultas Ilmu Keperawatan Universitas Indonesia, 2025)
Infertility often leads to stress, anxiety, and depression, significantly affecting the quality of life of affected couples. This study explored the sociodemographic and psychological factors influencing the quality of life among infertile couples undergoing in vitro fertilization (IVF) treatment in Malaysia, using a cross-sectional design. A total of 126 infertile couples were purposively sampled from three public hospitals offering IVF treatment. The Depression, Anxiety, and Stress Scale (DASS-21) measured psychological distress levels, while the Fertility Quality of Life (Ferti-QoL) scale assessed fertility-related quality of life. Data collection adhered to strict ethical standards, with confidentiality ensured. Participants provided informed consent and completed surveys independently in private settings to ensure unbiased responses. Statistical analyses, including t-tests, chi-square tests, and multiple linear regression, were employed to identify significant patterns and predictors. Results revealed that wives had significantly lower FertiQoL scores compared to husbands (p < 0.001). Wives also experienced higher levels of stress, anxiety, and depression as indicated by DASS-21 scores (p < 0.001). Regression analysis identified stress (p < 0.001), anxiety (p = 0.04), depression (p < 0.001), and gender (p = 0.02) as significant predictors of quality of life. Elevated levels of psychological distress were associated with a notable decline in quality of life, particularly among wives. These findings emphasize the importance of addressing mental health needs among couples undergoing IVF. Healthcare providers should focus on emotional preparedness and develop targeted strategies to reduce psychological distress, ultimately enhancing the overall quality of life during treatment. Keywords: infertility, psychological distress, quality of life. Abstrak Tekanan Psikologis dan Kualitas Hidup Pasangan Tanpa Anak yang Menjalani Pengobatan Infertilitas di Malaysia. Infertilitas sering kali menyebabkan stres, kecemasan, dan depresi, yang secara signifikan memengaruhi kualitas hidup pasangan yang terdampak. Studi ini mengeksplorasi faktor sosiodemografi dan psikologis yang memengaruhi kualitas hidup pasangan tidak subur yang menjalani perawatan IVF di Malaysia, menggunakan desain cross-sectional. Sebanyak 126 pasangan tidak subur dipilih secara purposive sampling dari tiga rumah sakit umum yang menyediakan layanan IVF. Depression, Anxiety, and Stress Scale (DASS-21) digunakan untuk mengukur tingkat tekanan psikologis, sementara skala Fertility Quality of Life (Ferti-QoL) menilai kualitas hidup terkait kesuburan. Pengumpulan data dilakukan mengikuti standar etik penelitian dengan menjaga kerahasiaan data dan privasi peserta. Peserta memberikan persetujuan tertulis dan menyelesaikan survei secara mandiri dan terisolasi untuk memastikan jawaban yang tidak bias. Analisis statistik, termasuk uji t, chi-square, dan regresi linier berganda, digunakan untuk mengidentifikasi pola dan prediktor yang signifikan. Hasil menunjukkan bahwa skor FertiQoL pada istri secara signifikan lebih rendah dibandingkan dengan suami (p < 0,001). Istri juga mengalami tingkat stres, kecemasan, dan depresi yang lebih tinggi seperti yang ditunjukkan oleh skor DASS-21 (p < 0,001). Hasil analisis regresi mengidentifikasi stres (p < 0,001), kecemasan (p = 0,04), depresi (p < 0,001), dan jenis kelamin (p = 0,02) sebagai prediktor signifikan kualitas hidup. Tingginya tingkat tekanan psikologis berbanding lurus dengan penurunan kualitas hidup yang nyata, terutama pada istri. Temuan ini menekankan pentingnya menangani kebutuhan kesehatan mental pada pasangan yang menjalani IVF. Penyedia layanan kesehatan harus lebih mengutamakan kesiapan emosional dengan mengembangkan strategi yang ditargetkan untuk mengurangi tekanan psikologis guna meningkatkan kualitas hidup selama perawatan. Kata Kunci: infertilitas, kualitas hidup, tekanan psikologis